ChemInform Abstract: Introduction of the 4, 4, 4‐Trifluorobut‐2‐ene Chain Exploiting a Regioselective Tsuji—Trost Reaction Catalyzed by Palladium Nanoparticles. Issue 32 (August 2015) - Hemelaere, Remy; Desroches, Justine; Paquin, Jean‐Francois
Abstract An effective process for the regioselective Tsuji—Trost reaction of 4, 4, 4‐trifluorobut‐2‐ene derived carbonate (I) and (VI), or acetate (VII) with aromatic alcohols, secondary amines, and malonate type C‐nucleophiles is developed.